Neonatal primary hyperparathyroidism masked by vitamin D deficiency. - Meeran, K; Husain, M; Puccini, M; Scott, H; Dionisi-Vici, C; Harvey, DR; Lynn, J; Thakker, R (1994)
Neonatal primary hyperparathyroidism is a life threatening disorder that is associated with severe hypercalcaemia, hypotonia, bone demineralization, fractures and respiratory distress. Treatment consists of total parathyroidectomy and without this affected infants will usually die by the age of three months. We report a patient with neonatal primary hyperparathyroidism who survived without fractures or parathyroidectomy to an age of nine months, and in whom the hypercalcaemia became masked by vitamin D deficiency. At surgery, four-gland hyperplasia was demonstrated and total parathyroidectomy followed by oral calcitriol treatment has restored well-being and normocalcaemia. An absence of skeletal complications, a survival beyond three months of age without parathyroidectomy and the masking of the hypercalcaemia by vitamin D deficiency represents a unique combination of metabolic abnormalities in a patient with neonatal primary hyperparathyroidism.